Literature Review: The Impact of Entrepreneurial Leadership on The Quality of Health Services - Hanafi, Yunisa Hasna; Ilyas, Yaslis (Syntax Corporation Indonesia, 2025)
The quality of health services plays a crucial role in achieving better health outcomes globally. Despite the availability of healthcare, poor service quality leads to millions of deaths annually. Entrepreneurial leadership, characterized by innovation, risk-taking, and strategic adaptability, is vital in improving service quality. This literature review examines the role of entrepreneurial leadership in enhancing healthcare service quality, particularly in hospitals. Secondary data was gathered from Google Scholar, PubMed, and ScienceDirect, focusing on studies published between 2020 and 2025. The review reveals that entrepreneurial leadership fosters innovation, increases work engagement, and improves hospital adaptability to evolving patient needs. The findings suggest that hospitals with entrepreneurial leaders can achieve continuous improvements in service quality by adapting to changes, enhancing efficiency, and fostering creativity within their teams. This research emphasizes the need for further studies to explore the direct impact of entrepreneurial leadership on healthcare service quality, as the current literature lacks in-depth analysis of this relationship.